CRITICAL ANALYSIS ON THE IMPACT OF HEALTHCARE POLICIES ON PHARMACEUTICAL ACCESS AND AFFORDABILITY IN PHARMACEUTICAL POLICY AND ECONOMICS - ‏1Majed Awad Maeed Alzahrani, 2‏Faisal Talal Alradadi, 3‏Waad Naser Alfaraj, ‏4Sultan Eid Alahmadi, 5‏Faisal Ahmed Al-Barqi Asiri, 6Mohammed Yahya Mohammed Almsabi, 7‏Rania Jaber Alshamrainy, ‏8Ahmed Hassan Abdullah AlQarni (Chelonian Research Foundation, 2022)
This article looks at the effect of well-being Healthcare policies s on pharmaceutical utilization and reasonableness through the focal point of pharmaceutical policies s and financial matters. It examines worldwide well-being approaches, looking at their effects on understanding how to use and the reasonableness of medications. The method includes comprehensively examining accessible information and introducing pictures, words, and pictures to legitimize the discoveries. The talk assesses the effect of well-being Healthcare policies s on drug stores and distinguishes issues of get-to and reasonableness. The choice gives critical knowledge and highlights challenges and openings for medical approaches and commerce. Proposals are summarized to address the issues recognized and to move forward with the reasonableness of solutions generally. Keywords: Healthcare policies, pharmaceutical access, affordability, pharmaceutical policy, economics